Effect of Three Different Aloe vera Gel-Based Edible Coatings on the Quality of Fresh-Cut “Hayward” Kiwifruits - Roberta Passafiume; Raimondo Gaglio; Giuseppe Sortino; Vittorio Farina (Foods, 2020)
In recent years, the market for minimally processed fruit has increased. Fresh-cut fruits are characterized by a short shelf life due to the processing phases that accelerate the ripening courses. The aim of this work is to analyze the effect on the quality of fresh-cut Hayward kiwis of three different edible coatings based on (1) Aloe vera gel, (2) Aloe vera gel + hydroxypropyl methylcellulose and (3) Aloe vera gel + lemon essential oil. Fruit firmness, weight loss, color, soluble solids content, titratable acidity, microbial load and sensory analysis were evaluated as fresh after 2, 4, 7 and 10 days. Aloe vera gel and Aloe vera gel + lemon essential oil maintained the best values, as they acted as a barrier to gas exchange and further reduced the microbial load. These results were confirmed by sensory analysis: Aloe vera gel + hydroxypropyl methylcellulose does not alter the natural taste of kiwi slices, Aloe vera gel + lemon essential oil gives the characteristic taste of lemon essential oil and Aloe vera gel gives an herbaceous taste. The Aloe vera gel, in combination with these additives, maintains the ability to preserve the quality of fresh-cut kiwifruit.